CONTINUAL QUALITY IMPROVEMENT CONTRIBUTING TO PROGRAMME LEARNING OUTCOMES IN GEOTECHNICAL ENGINEERING COURSE IN MALAYSIA - Mohamad Shakri Mohmad Shariff; Che Maznah Mat Isa, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This study investigates the effectiveness of Continual Quality Improvement (CQI) processes in aligning Course Learning Outcomes (CLOs) with Programme Learning Outcomes (PLOs) within a Geotechnical Engineering course in a Malaysian engineering program. Utilizing a qualitative methodology, the research analyzes data collected longitudinally over six semesters from the Outcome-Based Education (OBE) system, specifically focusing on CO-PO mapping. The study distinctly addresses two core PLOs: PLO1, which emphasizes Engineering Knowledge, and PLO4, which focuses on Investigation skills. Through comprehensive document analysis, this paper evaluates how targeted improvements in CLOs influence the attainment of these PLOs over time. The findings reveal that specific CQI interventions tailored to each PLO significantly enhance their respective learning outcomes. For PLO1, enhancements in teaching methodologies and curriculum alignment were most effective, while for PLO4, integrating research-based projects and improving experimental learning opportunities showed substantial benefits. The study proposes a refined CQI framework that offers strategic recommendations for curriculum development, assessment practices, and faculty development. By comprehending and implementing these recommendations, the goal is to narrow the gap between accrediting criteria and industry requirements, thereby improving student readiness and the overall quality of engineering education.